Hubungan Usia dan Dukungan Keluarga Dengan Kecemasan pada Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Beruntung Baru Kabupaten Banjar Tahun 2019 - Islami, Ridha; Zakiah, Zakiah; Suhrawardi, Suhrawardi (JURNAL KEBIDANAN BESTARI, 2021)
Abstract Anxiety is assessment and emotional response to something dangerous. Pregnancy can be a source of anxiety on pregnant women in the third trimester related to fear of pain in labor. Some of the factors that cause anxiety are age and family support. The purpose of this researce is to determine the correlation of age and family support with anxiety on third trimester pregnant women in Beruntung baru Public Health Center on 2019. Research Method used analytic survey method with Cross Sectional approach. Population of this research is third trimester pregnant women in the Beruntung Baru Public Health Center Banjar Regency on 2019. Sample is saturated, total sample are 63 people. Data collection using questionnaires. Data analysis using Chi-Square test. Results of 63 respondents are 17 people (27.0%) experienced anxiety in pregnancy, respondents with risky age are 10 people (15.9%), negative family support are 34 people (54.0%). Statistical test results there are relationship between age with anxiety (p = 0.003), family support with anxiety (p = 0.014). Conclusion of the research there was a correlation between age with anxiety and there are correlation between family support with anxiety on third trimester pregnant women in Beruntung Baru public health center on 2019. Keyword: Anxiety, Age, Family Support